Impurity metallic conduction below the critical concentration of metal-insulator transition in Fe1−xCoxSi. (10th May 2023) - Krishnan, M; Ganesan, V
Abstract: Analysis on very detailed measurements of resistivity ( ρ ) and thermoelectric power (S) of magnetic impurity (Co) substituted iron silicide (FeSi) has been presented in this report. The impurity valence electrons of Co dominate the whole physical properties at low temperatures below 35 K, below the critical concentration x c (≈0.02). The negative thermopower and the positive slope in the resistivity at low temperatures are exciting and show that the system is not entirely insulator below the critical concentration of metal–insulator transition ( x c ). So, due to the external impurity electrons, the system's magnetic ground state could change considerably compared to the parent compound FeSi. This report may help unveil the interesting low-temperature transport properties between x = 0 and x = 0.04 (Fe 1 − x Co x Si). Two band model and variable range hopping model were employed to explain the low-temperature electrical and thermal transport properties.